Deformation-Induced and Reaction-Enhanced Permeability in Metabasic Gneisses, Iona, Scotland: Controls and Scales of Retrograde Fluid Movement. (28th January 2021) - Dempster, Tim J.; Hollinsworth, Allan D.; McIntosh, Euan; Edgar, Shannon; Faithfull, John W.; Koehn, Daniel
Abstract : The spatial distribution of greenschist-facies retrograde reaction products in metabasic gneisses from Iona, western Scotland, has been investigated. The retrograde products may be broadly accounted for by a single reaction, but their different spatial and temporal development indicates that a series of reactions occur with significantly different scales of metasomatic transfer. After initial fluid influx linked to deformation-induced high permeability, reaction-enhanced permeability, coupled to cycling of fluid pressure during faulting, strongly controls the pervasive retrogression. Ca-plagioclase and pyroxene in the gneisses are replaced by albite and chlorite in pseudomorphic textures, and this is followed by localized epidotization of the albite. Two main generations of epidote are formed in the gneisses. Epidosite formation is associated with prominent zones of cataclasite indicating a strong link between faulting and fluid influx. In contrast, complete alteration of albite to epidote in the host metabasic gneisses is spatially complex, and areas of pervasive alteration may be constrained by both epidote-rich veins and cataclasites. In other instances, reaction fronts are unrelated to structural features. Volume changes associated with individual stages of the reaction history strongly control the localized distribution of epidote and the earlier more widespread development of chlorite and albite. Such behaviour contrasts with adjacent granitic gneisses where epidotization is restricted to local structural conduits. Many small-scale mineralized fractures with evidence of having previously contained fluids do not enhance the pervasive retrogression of the metabasic gneisses and represent conduits of fluid removal. Retrogression of these basement gneisses is dominated by a complex combination of reaction-enhanced and reaction-restricted permeability, kinetic controls on the nucleation of reaction products, changes in fluid composition buffered by the reactions, and periodic local migration of fluids associated with fault movements. This combination generates spatially complex patterns of epidotization that are limited by cation supply rather than fluid availability and alternations between focused and pervasive types of retrogression.